Micronutrients Analysis of Fresh and Canned “Agaricus Bisporus” and “Pleurotus Ostreatus” Mushroom Sold in Alexandria Markets, Egypt - A. Shbeeb, Doaa; Fawzi Farahat, Mohamed; Mohamed Ismail, Hanaa (International Journal of Nutrition, 2020)
Edible mushrooms form very nourishing meals especially for invalids, for they are easily digestible. They are consumed not only for their innate flavor and taste, but also for their important nutritional value, therefore, we analyzed the micronutrient contents of fresh and canned Agaricusbisporusand Pleurotusostreatus mushroom for their calcium, potassium and iron content. Fresh Agaricus was insignificantly higher in its calcium and iron contents (36.0 and 37.5 mg/100g; respectively) than Pleurotus(33.8 and 29.8 mg/100g) although the later was significantly higher in its potassium content (3890.4 mg/100g) versus 3102.9 in Agaricus. The micronutrient content of the canned Agaricus was higher than the canned cut Pleurotus. As these species of mushrooms are good sources of calcium, potassium, and iron, so they can be used as supplementary healthy foods for human nutrition.
Keywords: Mushroom; Agaricusbisporus; Pleurotusostreatus; Micronutrients